Shrinkage curvature of cracked reinforced concrete sections under load. (1st December 2021) - Scott, Richard; Whittle, Robin; Jones, Tony
Abstract: This paper describes an experimental program, which investigates the validity of using Expression 7.21 in Eurocode 2 for calculating shrinkage curvatures of loaded reinforced concrete beams cracked in flexure, this Expression having previously been validated for use with uncracked sections but not for cracked sections. The experimental method used a heating technique, which exploited the differing coefficients of expansion of limestone concrete and stainless steel reinforcement to impose simulated shrinkage strains on a range of rectangular beams of various sizes and reinforcement percentages. The results indicate that Expression 7.21 is valid for use with sections cracked in flexure but may overestimate curvatures by significant amounts. It is shown that improved estimates of curvature are given by using Expression 7.18 in conjunction with Expression 7.21 with the best results being obtained by setting β = 0.3 or by using an adjusted value for the cracking moment ( M cr ), as detailed in the paper.